THE ROLE OF ASSISTANT PERFORMANCE MODERATION ON THE EFFECT OF THE FAMILY HOPE PROGRAM ON POVERTY ALLEVIATION IN TANJUNGBALAI CITY - Dedeng Irawan (Proceeding International Seminar of Islamic Studies, 2021)
Social welfare for all the poor in the city of Tanjungbalai is the main goal of the mayor of Tanjungbalai. One of the efforts of the Tanjungbalai City Government to achieve poverty alleviation in Tanjungbalai City is by presenting a central government program, namely the Family Hope Program, which is one of the flagship programs of the Ministry of Social Affairs of the Republic of Indonesia, which in its implementation still often experiences problems due to a lack of knowledge of the program so as to To overcome this, a social assistant is appointed to assist in applying this assistance program. The research approach used is quantitative supported by primary and secondary data. The type of data used is primary data obtained through distributing questionnaires to direct PKH recipients. The data analysis technique starts from collecting information through a questionnaire in the form of a statement and at the final stage by drawing conclusions. The results of the research show that the variable of the Family Hope Program significantly affects the Poverty Alleviation variable in Tanjungbalai City so that the Tanjungbalai City government must be able to maintain this assistance program so that the people of Tanjungbalai City can be helped. Meanwhile, according to the research results, the companion's performance shows that significantly the companion performance variable moderates the relationship between the Hope Family Program and Poverty Alleviation in Tanjungbalai City, which means that the companion's performance can strengthen the implementation of PKH activities in the city of Tanjungbalai. Keywords: Family Hope Program, Companion Performance, Poverty Alleviation